Structural barriers to sexual and reproductive health care among Black and Latina cisgender and transgender U.S. women who use drugs: a qualitative study - Madina Agénor; Aisha Tipnis; Mikaela Byers; Tori Davis; Madeline Noh; Reagan Dunham; Kelly Reyna; Queen Adesuyi; Angela R. Bazzi; Katie B. Biello (BMC Health Services Research)
Abstract Background Black and Latina women and women who use drugs in the United States (U.S.) face multilevel barriers to receiving sexual and reproductive health (SRH) care that meets their needs. Although prior research has investigated barriers to SRH care among Black and Latina women in general, no study of which we are aware has examined how structural inequities shape the SRH care experiences of Black and Latina women who use drugs in particular in relation to multiple intersecting systems of oppression. Methods Using a stratified purposive sampling strategy, we conducted in-depth interviews (n = 18) with Black and Latina cisgender and transgender women aged 18–45 years who use drugs and had received SRH care in Boston, MA, Providence, RI, or Washington, DC in the last 12 months. Interviews were coded and themes were developed using a template style thematic analysis approach. All study activities were guided by a Community Advisory Board composed of six Black and Latina cisgender and transgender women who use drugs. Results Participants reported notable challenges accessing SRH services as a result of a lack of consistent health insurance, limited public transportation, high or unexpected costs, and criminalization by the legal system. Additionally, participants’ health care experiences were undermined by sexism, racism, transphobia, classism, heterosexism, fatphobia, and substance use stigma, which resulted in poor quality sexual, reproductive, and other health care and in delaying or avoiding care. In contrast, participants expressed a strong preference for receiving care from health care providers who were respectful, compassionate, and attentive to their needs. Moreover, participants reported more positive experiences receiving SRH care from health care providers who used a person-centered approach, who tended to share their racialized and gender identities, in community-affirming institutions. Conclusions Structural and collective efforts rooted in reproductive justice are urgently needed to address the precarious social and economic conditions, multiple intersecting systems of oppression, and criminal legal and health care practices that negatively impact the lives and SRH care of Black and Latina cisgender and transgender women who use drugs and, instead, foster health, healing, and well-being at the personal, community, and societal level.